Analysis of external personal dosimetry for external ex-posure to medical radiation workers in radiotherapy and nuclear medicine departments between 2019 and 2022 (Brazilian Journal of Radiation Sciences, 2024)
The National Cancer Institute from Chile possesses a wide variety of high-complexity equipment for cancer treatment and diagnosis that employs ionizing radiation with high and medium energy. Presently, the radiotherapy department is equipped with 5 clinical linear accelerators and one brachytherapy equipment, while the nuclear medicine department is equipped with a PET-CT, a single gamma camera, and a hospitalization room for betatherapy. A descriptive statistical analysis was conducted on the Personal Doses Equivalent Reports from medical radiation workers between 2019-2022. The analysis involved extracting Hp(10) and Hp(0.07) measurements from digital reports using the Python Pandas library, and a database was constructed. The annual set of data was selected for each department to describe their behavior concerning Hp(10) total since PD8 dosimeters had the highest circulation. Additionally, using the boxplot format for the Hp(10) and Hp(0.07) distributions, means, medians, minimums and maximums, interquartile ranges and outliers were analyzed.  While Hp(10) measurements exhibited an increase, Hp(0.07) measurements remained constant or experienced a decrease. All reported measurements were less than international tolerances. Finally, this initial descriptive statistical analysis enables the radiation safety officers to evaluate the applicability of inferential statistical analysis with stronger evidence and in an objective manner.